2011
DOI: 10.3402/pba.v1i0.7013
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses intestinal polyps in APC Min mice fed a high fat diet

Abstract: Colorectal cancer (CRC) is a leading cause of cancer deaths in the United States. Various risk factors have been associated with CRC including increasing age and diet. Epidemiological and experimental studies have implicated a diet high in fat as an important risk factor for colon cancer. High fat diets can promote obesity resulting in insulin resistance and inflammation and the development of oxidative stress, increased cell proliferation, and suppression of apoptosis. Because of the high consumption of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Obesity per se has also been shown to increase intestinal proliferation (Mao et al 2013), and data from our lab and others have shown that HFD can exacerbate tumorigenesis in several Apc models (Day et al 2013; Gravaghi et al 2008; Hata et al 2011; Huffman et al 2013; Pettan-Brewer et al 2011), including Apc -deficient Lgr5+-ISCs (Beyaz et al 2016). However, even when combined with obesity, Pten deficiency per se in Lgr5-ISCs, in the absence of Apc mutations, is insufficient to drive adenoma formation in these mice, even up to 15 mo of age.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Obesity per se has also been shown to increase intestinal proliferation (Mao et al 2013), and data from our lab and others have shown that HFD can exacerbate tumorigenesis in several Apc models (Day et al 2013; Gravaghi et al 2008; Hata et al 2011; Huffman et al 2013; Pettan-Brewer et al 2011), including Apc -deficient Lgr5+-ISCs (Beyaz et al 2016). However, even when combined with obesity, Pten deficiency per se in Lgr5-ISCs, in the absence of Apc mutations, is insufficient to drive adenoma formation in these mice, even up to 15 mo of age.…”
Section: Discussionmentioning
confidence: 92%
“…Obesity and diet are also strong regulators of CRC risk and progression in humans (Bardou, et al 2013; Cheskin and Prosser 2007; Giovannucci and Michaud 2007; Kim, et al 2006; Pischon, et al 2006; Schlesinger, et al 2015), and intestinal tumor development in rodent models (Beyaz, et al 2016; Day, et al 2013; Gravaghi, et al 2008; Hata, et al 2011; Huffman, et al 2013; Pettan-Brewer, et al 2011). Even prior to tumor initiation, obesity appears to ‘prime’ the normal intestinal epithelium toward tumor development, by promoting proliferation of ISCs and hypertrophy of the epithelium (Mao, et al 2013), while also altering the epigenomic landscape of the colonic epithelium in a manner resembling cancer progression (Li, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has a variety of pharmacologic properties. It has been demonstrated to have systemic anti-inflammatory activity and beneficial effects in several types of cancers both in animals and humans [112][113][114][115][116][117], and in individuals with dermatitis [118], Crohn's disease [119], and ulcerative colitis [120]. In addition, curcumin has been shown to improve metabolic disorders associated with hyperlipidemia and hyperglycemia [121][122][123][124][125].…”
Section: Polyphenol (Curcumin)mentioning
confidence: 99%
“…In fact, curcumin was found to be one of the most effective chemopreventive agents against CRC [31]. Recent reports on the antitumor effect of curcumin in APC Min mice fed a high-fat diet [32] and in db/db obese mice [33] suggest that curcumin might also be effective in the prevention of obesity-associated colon cancer.…”
Section: Introductionmentioning
confidence: 99%